WORKING WOMEN PREFERENCE AND SATISFACTION OF USING THE READY-TO-EAT FOOD PRODUCTS IN CHENNAI CITY - Ezhilarasi, A. (International Journal of Research -GRANTHAALAYAH, 2021)
Aim: The present study aims to assess the working women’s Preference and satisfaction of using the Ready-to-Eat products in Chennai city. Data Sources: The study utilized primary and secondary sources of data. The secondary sources of data were obtained from the research articles, news- papers, and weekly magazines. The primary data sources were collected from the working women who are using the Ready-to-Eat food products in the study region—the primary data obtained from working women’s workplaces and their residence place. Sampling Technique & Size: The study employed the convenience sam- pling method. Overall, 300 structured questionnaires were distributed, out of which 291 filled questionnaires were collected from the working women. Findings: The study found that the working women positively preferred for consumption of Ready-to-Eat food products. The working women’s felt that the ready-to-eat food products readily available for the preparation of food prod- ucts. The working women also viewed that the availability of ready-to-eat food products quickly. The study also found that the working women are delighted with the consumption of Ready to Food products in the study area.